2018
DOI: 10.3897/zookeys.801.22395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ultrastructure of cells and cuticle in the anterior chamber and papillate region of Porcellio scaber (Crustacea, Isopoda) hindgut

Abstract: Isopod hindgut consists of two anatomical and functional parts, the anterior chamber, and the papillate region. This study provides a detailed ultrastructural comparison of epithelial cells in the anterior chamber and the papillate region with focus on cuticle ultrastructure, apical and basal plasma membrane labyrinths, and cell junctions. Na+/K+-ATPase activity in the hindgut epithelial cells was demonstrated by cytochemical localisation. The main difference in cuticle ultrastructure is in the thickness of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 68 publications
1
11
1
Order By: Relevance
“…117 Beneath the epithelial cells typically lays the basal lamina, which can have a thickness from 100-300 nm in isopods (being regarded as outstandingly thick for invertebrates). 116 The basal lamina is supposed to act like a charged sieve, in which the passage of macromolecules depends on its charge and porosity. In insects, for example, it has been shown that the basal lamina of the midgut prevented the passage of 6-15 nm gold nanoparticles.…”
Section: The Gut Barrier In Invertebrate Speciesmentioning
confidence: 99%
“…117 Beneath the epithelial cells typically lays the basal lamina, which can have a thickness from 100-300 nm in isopods (being regarded as outstandingly thick for invertebrates). 116 The basal lamina is supposed to act like a charged sieve, in which the passage of macromolecules depends on its charge and porosity. In insects, for example, it has been shown that the basal lamina of the midgut prevented the passage of 6-15 nm gold nanoparticles.…”
Section: The Gut Barrier In Invertebrate Speciesmentioning
confidence: 99%
“…The ultrastructure of SJs in tergite epidermis of intermoult adult P. scaber was characterised and compared with SJs in the hindgut epithelium of the same species ( Bogataj et al 2018 ) and with pleated SJs in different ectodermal epithelia of adult specimens of other arthropod species ( Happ and Happ 1970 ; Lane and Skaer 1980 ; Noirot-Timothée and Noirot 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…The adult epithelial cells show abundant mitochondria in the apical region, and infolded membranes with lateral junctions. Such features are associated with the reabsorption of water and ions in several arthropods, including insects, crustaceans and millipedes (Mykles 1979;Phillips et al 1987;Nardi et al 2006;Nardi et al 2009;Nardi et al 2016;Bogataj et al 2018). Moreover, the fibres structures of the epithelial cells are more developed in adults than in larvae, and have also been proposed to be involved in the intracellular transport of water and ions in different crustacean groups (Komuro and Yamamoto 1968;Witkus et al 1969;Vernon et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Since the fibres structures have two potential roles (intracellular transport and mechanical connection), it raises one question: are both roles inclusive or mutually exclusive? Bogataj et al (2018) suggested both roles for the hindgut epithelial cells of the woodlouse. In our opinion, the hindgut epithelial cells of the larvae and adults probably are tendon cells, connecting the muscular action with the cuticle, but in adults the same cells also develop a sophisticated transport system for osmoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation